“Right to Try” Legislation Moving Through Congress: But Drug Companies and Some Patient Groups Want Changes - Barlas, Stephen (P T, 2017)
State “Right to Try” laws, which allow terminally ill patients to seek investigational treatments under certain circumstances, have created pressure for Congress to follow up with a federal law. Though facing opposition from patient advocates and the drug industry, a bill passed by the Senate is now making its way to the House.